Which educational messengers do medical students prefer for receiving healthinformation? Development and psychometrics of using health messengers questionnaire - Zahra Karimian; Mehrvash Moradi; Nahid Zarifsanaiey; Sara Kashefian-Naeeini (BMC, 2024)
Abstract Introduction Individuals vary in their selection of health messengers. This research aimed to construct an instrument to measure the preferences of medical students in selecting health messengers and in the next step to validate the aforementioned questionnaire. Method This research is a descriptive survey with an approach to construct a questionnaire. The statistical population included all students studying at Shiraz University of Medical Sciences in March to June 2022 in the academic year 2021-2022. 500 participants were involved in the study. To determine the types of health messengers and review the texts, a group of 15 primary items consisting of the 6 components of academic sources (2-items), formal news sources (2-items), mass media (3-items), internet search (2-items), social networks and messenger applications (4-items), and informal conversation (2-items) were compiled. A 4-point scale was developed the content validity of which was confirmed using CVI and CVR method and the reliability index was calculated to be 0.818. Factor analysis was also used to determine the construct validity and factor loading of each item. Results The research covers university students in different medical fields. Using factor analysis, together with KMO = 0.810 and Bartlett's sphericity index P < 0.0001, saturation and the suitability of the test were confirmed. Students' preferences based on factor load were social media (28.92%), official and unofficial health sources(10.76%), academic sources (9.08%), internet search (8.18%), and mass media (7.13%), respectively. Among social media, Telegram (0.85) had the highest factor load followed by Instagram (0.79), and WhatsApp (0.71). Conclusion Medical students are always on the move and naturally prioritize mobile-based methods. They prefer messengers that are free from time and space restrictions. The widespread availability of mobile devices and the ability to search for and access information make it easier to test health information. Therefore, in health policy, attention should be paid to the virtual capabilities, especially mobile-based approaches.